Burnout in the intensive care unit professionals: A systematic review. Issue 50 (December 2016) - Chuang, Chien-Huai; Tseng, Pei-Chi; Lin, Chun-Yu; Lin, Kuan-Han; Chen, Yen-Yuan
Abstract: Background: Burnout has been described as a prolonged response to chronic emotional and interpersonal stress on the job that is often the result of a period of expending excessive effort at work while having too little recovery time. Healthcare workers who work in a stressful medical environment, especially in an intensive care unit (ICU), may be particularly susceptible to burnout. In healthcare workers, burnout may affect their well-being and the quality of professional care they provide and can, therefore, be detrimental to patient safety. The objectives of this study were: to determine the prevalence of burnout in the ICU setting; and to identify factors associated with burnout in ICU professionals. Methods: The original articles for observational studies were retrieved from PubMed, MEDLINE, and Web of Science in June 2016 using the following MeSH terms: "burnout" and "intensive care unit". Articles that were published in English between January 1996 and June 2016 were eligible for inclusion. Two reviewers evaluated the abstracts identified using our search criteria prior to full text review. To be included in the final analysis, studies were required to have employed an observational study design and examined the associations between any risk factors and burnout in the ICU setting. Results: Overall, 203 full text articles were identified in the electronic databases after the exclusion of duplicate articles. After the initial review, 25 studies fulfilled the inclusion criteria. The prevalence of burnout in ICU professionals in the included studies ranged from 6% to 47%. The following factors were reported to be associated with burnout: age, sex, marital status, personality traits, work experience in an ICU, work environment, workload and shift work, ethical issues, and end-of-life decision-making. Conclusions: The impact of the identified factors on burnout remains poorly understood. Nevertheless, this review presents important information, suggesting that ICU professionals may suffer from a high level of burnout, potentially threatening patient care. Future work should address the effective management of the factors negatively affecting ICU professionals.